A SUSTAINABLE MANUFACTURING STRATEGY FRAMEWORK: THE CONVERGENCE OF TWO FIELDS - Lanndon A. Ocampo,; Eppie E. Clark, (Asian Academy of Management Journal, 2015)
Pressing concerns about the sustainability of products and processes have compelled the manufacturing industry to transition from making mere economic-based decisions to envisioning more holistic goals encompassing economic, environmental and social perspectives. The intriguing results of this transformation include the development of various sustainability programs and initiatives that has increased for three decades. The myriad of research in this area focuses on creating opportunities that would minimize, if not eliminate, the impact of manufacturing activities on the natural environment and society. However, previous approaches seemingly detach their association to the competitive function of manufacturing. Maintaining competitiveness while pursuing sustainability has drawn interest from practitioners, but this area is inadequately explored in the current literature. Current research directions on sustainability in the manufacturing industry lack foundations on exploring mechanisms that maintain or improve the competitive function of manufacturing. The integration of sustainability issues into manufacturing strategy (MS) implies complex decision-making in manufacturing. Thus, this paper proposes a framework in formulating MS that addresses sustainability issues while taking into account the competitive function of manufacturing. The framework integrates classical theories of MS and sustainability issues derived from previous works. The proposed framework provides guidance for the decision-making of practitioners and researchers in developing a sustainable manufacturing strategy (SMS). This contributes to manufacturing planning at the firm level.